Effect of An Evidence-Based Nursing Intervention on the Diagnosis of Oral Mucositis in the Pediatric Stem Cell Transplant Unit - Seyda Avci; Hatice Yildirim Sari (Elsevier, 2019)
Objective: This quasi-experimental, single-group study with a pre- and post-repeated measures design was carried out at the Pediatric Stem Cell Transplant Unit of a University Hospital. The study was aimed at investigating the effect of an evidence-based nursing intervention program, held for nurses providing care for pediatric stem cell transplant patients, on their skills in diagnosing oral mucositis (OM). Methods: Before training, data were collected from all the nurses using a sociodemographic characteristics questionnaire. Six patients who were admitted to the clinic and started chemotherapy (CT) were followed up for a maximum of 1 month during their hospitalization to find whether the diagnosis of OM was performed. During the intervention stage, the researcher provided nurses with training on the importance of the use of evidence-based research results in the clinic, including evidence regarding OM. After the training, the records of six patients who were admitted to the clinic and started CT were tracked for up to 1 month during their hospitalization to find whether the diagnosis of OM was performed. Results: At the end of the study, the rate of OM diagnosis was performed by nurses, which was 2.8% before the program and increased to 8.7% after the program. The difference between the percentages of performing OM diagnosis by the nurses before and after the program was 5.9%, which was considered statistically significant (χ2 = 11.004, P < 0.01). The postprogram rate of diagnosis of OM was 3.12 times higher (212% increase) than the preprogram rate (P < 0.01). Conclusions: One of the most important recommendations of the present study is to provide regular and continuous training sessions for nurses to improve and update their knowledge on oral care. It is also concluded that the establishment of oral diagnosis as a follow-up parameter, similar to vital signs in the clinic, will enable nurses to improve their skills in performing daily diagnosis and keeping proper records of the patients' outcomes.